Entrepreneurial Intention of Students in Jabodetabek Region - Pauline H. P. Tan; Tharis Tiona; Dewi Wuisan; Kyle Christopher Suhaili; Danet Arya Patria (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study aims to further analyze the influence of Subjective Norm, Perceived Behavioral Control, Self-Efficacy, and Entrepreneurship Education on Entrepreneurial Intention among students majoring in Entrepreneurship in the Greater Jakarta area (Jabodetabek). The research employs a causal or explanatory design, aiming to test hypotheses. A quantitative approach is adopted in this study. The data collected constitute primary data obtained through an online questionnaire. The study utilizes a non-probability sampling technique, specifically purposive sampling, in which the sample is selected based on specific criteria, namely students majoring in Entrepreneurship in Jabodetabek. The total sample size is 167 respondents. The questionnaire responses were measured using a Likert scale. Based on the research findings, it can be concluded that Perceived Behavioral Control, Self-Efficacy, and Entrepreneurship Education have a positive and significant influence on the Entrepreneurial Intention of students majoring in Entrepreneurship in Jabodetabek. However, Subjective Norm does not have an effect on the Entrepreneurial Intention of these students